a, the Pengaruh Profitabilitas, Intensitas Modal dan Kompetensi Komisaris Independen Terhadap Penghindaran Pajak - Purwaningsih, Eny; Mardiana, Anis (CV. Kalimasada Group, 2023)
Tax avoidance is a right that does not violate the law (legal), but on the government side, tax avoidance is undesirable becauseit will reduce revenue for the state. so that the purpose of this study is to find out empirically about the effect of profitability,capital intensity, and competence of independent commissioners on tax avoidance either partially or simultaneously in food andbeverage manufacturing sub-sector companies listed on the Indonesia Stock Exchange in the 2016-2020 period. This studyuses a type of causal research which is used to determine the relationship between cause and effect on two or more variables. Thesample in this study is a manufacturing company in the food and beverage sub-sector listed on the Indonesia Stock Exchangefor the 2016-2020 period using the purposive sampling method. There are 14 companies that meet the criteria of the researchsample, so the sample is 70 financial statements. The results showed that partially there was a significant and significant effectof the profitability and capital intensity variables on tax avoidance, while the independent commissioner's competence variablehad no effect on tax avoidance. Simultaneously there is an effect of profitability, capital intensity, and competence of independentcommissioners on tax avoidance.